Ocular Findings in COVID-19 Patients: A Review of Direct Manifestations and Indirect Effects on the Eye - Federica Bertoli; Daniele Veritti; Carla Danese; Francesco Samassa; Valentina Sarao; Nicolò Rassu; Tommaso Gambato; Paolo Lanzetta (Journal of Ophthalmology)
The novel pandemic coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has challenged the medical community. While diagnostic and therapeutic efforts have been focused on respiratory complications of the disease, several ocular implications have also emerged. SARS-CoV-2 RNA has been found in tears of the infected patients, and reports suggest that the ocular surface could serve as a portal of entry and a reservoir for viral transmission. Clinically, COVID-19 has been associated with mild conjunctivitis, which can be the first and only symptom of the disease. Subtle retinal changes like hyperreflective lesions in the inner layers on optical coherence tomography (OCT), cotton-wool spots, and microhemorrhages have also been reported. In addition, COVID-19 has been associated with an increased incidence of systemic diseases like diabetes mellitus and Kawasaki disease, which are particularly relevant for ophthalmologists due to their potentially severe ocular manifestations. Several treatment strategies are currently under investigation for COVID-19, but none of them have been proved to be safe and effective to date. Intensive care unit patients, due to risk factors like invasive mechanical ventilation, prone position, and multiresistant bacterial exposure, may develop ocular complications like ocular surface disorders, secondary infections, and less frequently acute ischemic optic neuropathy and intraocular pressure elevation. Among the array of drugs that have shown positive results, the use of hydroxychloroquine and chloroquine has raised a concern due to their well-known retinal toxic effects. However, the risk of retinal toxicity with short-term high-dose use of antimalarials is still unknown. Ocular side effects have also been reported with other investigational drugs like lopinavir-ritonavir, interferons, and interleukin-1 and interleukin-6 inhibitors. The aim of this review was to summarize ophthalmological implications of SARS-CoV-2 infection to serve as a reference for eye care and other physicians for prompt diagnosis and management.